Psychological predictors of quality of life among Jordanian cancer patients' caregivers. Issue 11 (17th October 2022) - Alnajar, Malek; Mosleh, Sultan; Almalik, Mona; Darawad, Muhammad
Abstract: Objective: The caregivers who provide care for patients with cancer often experience emotional and psychological stressors and burdens that could be influenced by several factors, including the cultural context. This study examines the level of emotional distress and burden and their effect on the quality of life (QOL) of Jordanian cancer patients' caregivers. Methods: A cross‐sectional survey was conducted among 257 family caregivers of patients at various stages of cancer. Results: The average age of caregivers was 37.5 years (SD = 12.2). Most caregivers (145; 59.2%) were female and married (168; 68.6%). About a quarter were partners (32.2%) and lived with their patients (137; 55.9%). Caregivers with a reduced overall Caregiver Quality of Life Index‐Cancer (CQOLC) score were more likely to be older, the parents of the patients, and living with patients in the same house. A significant negative relationship was found between caregivers' CQOLC and Zarit Burden Interview ( r = −0.7, p = 0.001), anxiety ( r = −0.69, p = 0.001), and depression ( r = −0.42, p = 0.03) scores. Multiple linear regression analysis revealed that burden, anxiety, and depression scores were independent predictors and explained 63% of the variance in the total CQOLC score of caregivers. Conclusion: Cancer caregivers are at elevated risk of poor QOL. Despite participants' low perception of the burden level, this study provides preliminary results for policymakers and medical practitioners to foster a comprehensive platform supporting cancer caregivers. Moreover, identifying the caregivers' readiness to provide the needed care and the availability of supportive resources, as a clinical routine, is strongly recommended.